Significant polyomic and functional upregulation of the PAPP‐A/IGFBP‐4/5/IGF‐1 axis in chronic rhinosinusitis with nasal polyps. Issue 4 (12th January 2020) - Mueller, Sarina K.; Nocera, Angela L.; Workman, Alan; Libermann, Towia; Dillon, Simon T.; Stegmann, Achim; Wurm, Jochen; Iro, Heinrich; Wendler, Olaf; Bleier, Benjamin S.
Abstract : Background: Chronic rhinosinusitis with nasal polyps (CRSwNP) is associated with epithelial expansion and polyp survival. However, the molecular mechanism of this aberrant proliferation is unclear. The purpose of this study was to interrogate derangements of the pappalysin‐A/insulin‐like growth factor binding protein/insulin‐like growth factor‐1 (PAPP‐A/IGFBP‐4/5/IGF‐1 axis) as a major contributing factor to polyp growth in CRSwNP. Methods: Matched tissue and exosomal proteomic arrays including PAPP‐A, IGFBP‐4, IGFBP‐5, and IGF‐1 were quantified using aptamer‐based methods/Western blots for proteomic analysis and whole‐transcriptome sequencing/quantitative polymerase chain reaction (qPCR) for transcriptomic analysis in CRSwNP and control patients. Functional PAPP‐A assays were then performed in both tissue and exosomes (set 1: n = 20 per group; validation set 2: n = 26 per group). Results: Tissue and exosomal PAPP‐A was significantly overexpressed in CRSwNP compared to controls on both a transcriptomic and proteomic level ( p < 0.0001). Known inhibitors of PAPP‐A (stanniocalcin‐1/‐2) were significantly downregulated ( p < 0.0001) as were PAPP‐A cleavage products (IGFBP‐5 p < 0.0001). PAPP‐A function was shown to be increased 5‐fold to 6‐fold in tissue and exosomes. Conclusion: Upregulated tissue and exosomal PAPP‐A signaling is significantly associated with CRSwNP and may be an important factor in the promotion of epithelial proliferation and polyp growth. These data lend further support to the emerging concept of exosomal functional and polyomic analyses as a method to study sinonasal pathology.